Productivity growth and convergence in agriculture and manufacturing - Martin, Will, 1953- 1953- (Policy research working paper, 1999)
The growth of agricultural productivity is widely believed to be low. But this study finds the productivity rate in agriculture to be higher than that in manufacturing, both on average and for groups of countries at different stages of development. This suggests that a large agricultural sector need not be a disadvantage for growth performance, and may be an advantage